Culturability of potential pathogenic bacteria in a co-digestion anaerobic digester system - Johnson, Shannon (My University, 2018)
Anaerobic digestion (AD) has the potential to reduce organic wastes and produce renewable energy from the degradation of organic materials to produce biogas. However, mixed substrate anaerobic digesters may create a suitable environment for opportunistic pathogenic bacteria. The fate of potential bacterial pathogens has been studied in manure-based digesters but their survival is not well understood when digesters are co-fed with food waste. Mixed substrates may change internal conditions and subsequently pathogen survival, resulting in concerns for general environmental health. The purpose of this study was to introduce and enumerate potentially pathogenic bacteria in a bench-scale AD system while analyzing possible relationships between colony growth with typical AD parameters: temperature, pH, and volatile fatty acids (VFAs). Food waste was utilized as a substrate and percolate (a manure surrogate) was used as an inoculum to examine the survival of five species of bacteria (Campylobacter jejuni, Staphylococcus aureus, Salmonella enterica, Enterococcus faecalis, and Escherichia coli) that were selected on likelihood of entering a digester or that they are indicators for groups potentially located in digesters. It is hypothesized that incomplete acidogenesis – from mixed substrates – may increase VFAs, lower pH, and therefore decrease pathogen survival. A modified membrane filtration method, with selective and differential media, were used to enumerate the microorganisms. In the Enterococcus spp. experimental growth system, linear regression analyses revealed that there is a relationship of colony reduction with: temperature, pH, and total VFAs. The reduction of four of the five organisms, early in AD, indicates that co-fed digesters can reduce pathogens and lower environmental health risks.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science of Biology
Keywords: Biogas; Anaerobic bacteria--Growth